2015
DOI: 10.1002/2014jd022580
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term and seasonal variability of the aerosol optical depth at Mount Kasprowy Wierch (Poland)

Abstract: This paper presents the results of long-term observations of direct solar radiation, to determine aerosol optical depth (AOD), made with a Linke-Feussner actinometer at the Tatra Mountain Meteorological Observatory on Mount Kasprowy Wierch (1991 m above sea level, 49.233°N, 19.982°E). To this end, broadband direct solar flux (0.29-2.9 μm) and wideband solar radiation measured with OG530 and RG630 filters are used to estimate the broadband and wideband (0.53-0.63 μm) AOD. The inversion algorithm used is based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 45 publications
(70 reference statements)
0
25
0
Order By: Relevance
“…In Poland, the growing trend in SD since the early 1980s can be explained not only by changes in cloud cover but also by a decrease in the amount of aerosols in the atmosphere, the highest rate of which occurred in the years 1992–1997 (Figure 10). This is confirmed by the results of studies of other authors who analysed changes in atmosphere transparency using ground data (Weller and Gericke, 2005; Ruckstuhl et al ., 2008; Ohvril et al ., 2009; Markowicz and Uscka‐Kowalkowska, 2015). The period of strong industrialization, especially in south‐west Poland (Lower and Upper Silesia, Krakow agglomeration) contributed to high concentrations of air pollution that are visible in the first half of the 1980s (Figure 11a).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…In Poland, the growing trend in SD since the early 1980s can be explained not only by changes in cloud cover but also by a decrease in the amount of aerosols in the atmosphere, the highest rate of which occurred in the years 1992–1997 (Figure 10). This is confirmed by the results of studies of other authors who analysed changes in atmosphere transparency using ground data (Weller and Gericke, 2005; Ruckstuhl et al ., 2008; Ohvril et al ., 2009; Markowicz and Uscka‐Kowalkowska, 2015). The period of strong industrialization, especially in south‐west Poland (Lower and Upper Silesia, Krakow agglomeration) contributed to high concentrations of air pollution that are visible in the first half of the 1980s (Figure 11a).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…However, on a longer period of 30 years (1980 to 2010) Nabat et al suggested that aerosol changes can explain around 80% of the brightening over Europe, based on simulations with a regional aerosol climate model driven with reanalysis data, with the direct aerosol effect dominating the magnitude of the simulated brightening. From long‐term records of direct solar radiation at a high altitude site in the Tatra Mountains (Poland) away from local sources, increases in AOD from 1964 to 1983 and subsequent declines from 1984–2003 were inferred, that fit to the SSR dimming and brightening, respectively . Dimming and brightening has also been consistently detected at the Izana station on the Canary Islands both under all sky and clear sky conditions, indicative of aerosol as a major contributor .…”
Section: Variations Of Solar Radiation Over Land Surfacesmentioning
confidence: 88%
“…BAOD is estimated on the basis of broadband direct shortwave radiation measurements according to Markowicz and Uscka-Kowalkowska (2015) methodology. BAOD is defined by means of the following equation (Qiu, 2001):…”
Section: Methodsmentioning
confidence: 99%
“…Mean absolute errors change from ±0.01 to ±0.03 for WAOD and from ±0.01 to ±0.04 for BAOD. As part of the BAOD conversion to an air mass of 2, the AOD at 500 nm (τ 500 ) is estimated as follows: (1) simulation of aerosol-free spectral flux based on MODTRAN, (2) estimation of the Angstrom exponent from long-term mean at Belsk AERONET station (see Markowicz & Uscka-Kowalkowska, 2015), (3) computation of spectral aerosol transmission…”
Section: Methodsmentioning
confidence: 99%